Chelate EDDHA to correct the iron deficiency in Italian lemon trees (Citrus limon (L.) Osbeck) - Puente-Ramírez, Juan Valentín; Rivera-Ortiz, Patricio; Silva-Espinosa, José Hugo; Andrade-Limas, Elizabeth (REVISTA TERRA LATINOAMERICANA, 2022)
Citriculture is one of the most important productive activities in the State of Tamaulipas, Mexico. However, in most orchards the yields of these fruit trees are low and frequently of poor quality due to a low supply of iron and other micronutrients. The calcareous characteristics of the soils such as a moderately alkaline pH –around 8– and a calcium carbonate content higher than 40% induce the precipitation of iron in the form of oxides and hydroxides, causing low availability of Fe for the plant. Therefore, the objective of this work was to evaluate the effect of the FeEDDHA chelate applied to the soil. In our study we used 25-year-old Italian lemon trees (Citrus limon (L.) Osbeck) grafted on sour orange rootstocks, with visual symptoms of iron deficiency and severe and persistent yellowing of new leaves. The application of different concentrations of FeEDDHA chelate (50, 100 and 150 g tree-1) to the soil and the control treatment were evaluated. We applied FeEDDHA to the soil with the purpose of determining the most appropriate dose of the chelator to correct the iron deficiency in Italian lemon trees under calcareous soil conditions of the Central zone of the State. The application of the chelate to the soil in doses between 50 and 100 g tree‑1 of FeEDDHA increased the SPAD index in the leaves, corrected the Fe deficiency in the trees, and significantly increased the foliar concentration of Fe to an optimal level (77 mg kg-1 Fe), the fruit yield (40 Mg ha-1) and the economic income. In addition, the application of a higher dose, 150 g tree-1 of FeEDDHA, did not significantly increase iron assimilation and fruit production in Italian lemon trees.